1989
DOI: 10.1093/oxfordjournals.aje.a115175
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Heritability and Common Environmental Components of Resting and Stressed Blood Pressures, Lipids, and Body Mass Index in Utah Pedigrees and Twins

Abstract: The relative contributions of genes and shared environment to cardiovascular risk factors were studied in twins and pedigrees in 1983-1985. Sitting, standing, isometric hand grip, bicycling, and mentally stressed (serial subtraction) blood pressures were obtained from 146 male monozygous twins, 162 male dizygous twins, and 1,102 healthy adults in 67 Utah pedigrees. Fasting total plasma cholesterol, triglycerides, high density lipoprotein cholesterol (HDL), and body mass index were also measured. Heritability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
142
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(153 citation statements)
references
References 0 publications
11
142
0
Order By: Relevance
“…Our heritability estimates for BP during HUT fall in the middle of the range reported by others. Hunt et al 42 found heritability estimates for standing BP that ranged from 0.08 to 0.16 for SBP and from 0.11 to 0.21 for Our results from the PCA indicate that multiple measurements of BP can be reduced to three interpretable components that represent (1) the overall effects of BP at rest and during HUT (i.e., 'general BP'), (2) 'pulse pressure' and (3) 'BP reactivity'. The three extracted components represent different aspects of BP during HUT such that each of these factors is distinct and uncorrelated with the others.…”
Section: Discussionmentioning
confidence: 99%
“…Our heritability estimates for BP during HUT fall in the middle of the range reported by others. Hunt et al 42 found heritability estimates for standing BP that ranged from 0.08 to 0.16 for SBP and from 0.11 to 0.21 for Our results from the PCA indicate that multiple measurements of BP can be reduced to three interpretable components that represent (1) the overall effects of BP at rest and during HUT (i.e., 'general BP'), (2) 'pulse pressure' and (3) 'BP reactivity'. The three extracted components represent different aspects of BP during HUT such that each of these factors is distinct and uncorrelated with the others.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed all studies on BP heritability including subjects older than 5 years of age, where mean age was reported and a Falconer heritability estimate 28 could be computed. 26,[29][30][31][32][33][34][35][36][37][38] These estimates are plotted versus age in Figure 3, which also shows the fit from the locally-weighted regression analysis. 39,40 The amount of fitting that was done, is equivalent to 4 degrees of freedom.…”
Section: Discussionmentioning
confidence: 99%
“…Especially a direct effect of BMI on BP could lead to an overestimation of BP heritability, 9 since BMI itself is highly heritable. 11 Because of this, it is very important to disentangle the influence of BMI, genetic influences and environmental influences in the variance of BP. Allison et al 10 have elegantly shown in middle-aged women how multivariate genetic modelling of twin data can be used to put the impact of an influence of BMI on BP into perspective with the genetic and environmental influences on BP per se.…”
Section: Introductionmentioning
confidence: 99%
“…Low concentrations of HDL-cholesterol (HDL-C) are a strong and independent risk factor for coronary heart disease (1). About 50% of the variation in plasma level HDL-C is believed to be genetically determined (2,3). ATP binding cassette transporter 1 gene (ABCA1, Genbank ID NM_005502, alias: ABC1; CERP; ABC-1) is one of the major genes modulating plasma HDL-C concentrations, and underlies two genetic diseases with low HDL-C: Tangier disease (MIM 205400) and familial HDL deficiency (MIM 604091) (4).…”
Section: Introductionmentioning
confidence: 99%